Intervenciones de enfermería en el paciente con artrosis basadas en la teoría de Callista Roy - Ramos Ramos, Rocío Pilar (2020)
This bibliographic review has the purpose of determining the nursing interventions applicable in the adult with osteoarthritis according to the theory of Callista Roy; A disease that is revealed primarily in the synovial membrane of diarthrodial joints, causing chronic inflammation with structural damage to articular cartilage, bone, ligaments and optionally extra-articular involvement with involvement in different organs and systems. The knee, hip and hands constitute the joints affected in the highest percentage; associated with several risk factors and with multiple options for their treatment, causing consequences that affect from independence to disability with repercussions on the adaptation and adherence to treatment, due to difficulty in mobility, inflammation and rigidity that causes changes in their lifestyle. 100 bibliographic sources from different databases were reviewed, in which aspects related to the subject were checked; Inclusion and exclusion criteria were applied, finally considering all 39 bibliographic sources, from which 12 were used for the triangulation process; obtaining as essential coincidences of 5 authors in the focal, contextual and residual stimuli; 7 authors referring to adaptive modes; physiological, self-concept, role function mode and interdependence mode. Based on the results, diagnostic labels, outcome, and interventions were determined with the NANDA-NOC-NIC taxonomy that could occur in this type of patients in relation to the Callista Roy model.